2023
DOI: 10.25092/baunfbed.1180304
|View full text |Cite
|
Sign up to set email alerts
|

TGA destekli sorgulama temelli öğretimin akademik başarıya ve bilimsel sorgulama becerisine etkisi

Abstract: Bu çalışmada elektrik ünitesinde tahmin-gözlem-açıklama (TGA) destekli sorgulamaya dayalı öğretimin öğrencilerin akademik başarısı ile bilimsel sorgulama becerilerine etkisinin araştırılması hedeflenmiştir. Bu çalışmada araştırma yöntemi olarak ön test-son test eşleştirilmiş kontrol gruplu yarı deneysel yöntemden yararlanılmıştır. Bu çalışma 2021-2022 eğitim öğretim yılı Marmara bölgesinde bir devlet ortaokulunun 6. sınıf seviyesinde okuyan toplam 26 öğrenci ile yapılmıştır. Çalışmanın uygulama grubu (n=13) ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…The main reason for this success is thought to be related to the decrease in the course hours of the Calculus-I course in the current curriculum compared to the previous program. In parallel with the findings of the study, it has been argued that practice in derivative learning positively affects academic achievement (Sağırlı, Kırmacı & Bulut, 2010). Besides, in the quasi-experimental study conducted by Çekmez and Baki (2019), the effect of dynamic software used for application in the learning of the geometric interpretation of the derivative was examined and it was concluded that the experimental group students who were subjected to the application had higher academic success.…”
Section: Discussion Conclusion and Suggestionssupporting
confidence: 54%
“…The main reason for this success is thought to be related to the decrease in the course hours of the Calculus-I course in the current curriculum compared to the previous program. In parallel with the findings of the study, it has been argued that practice in derivative learning positively affects academic achievement (Sağırlı, Kırmacı & Bulut, 2010). Besides, in the quasi-experimental study conducted by Çekmez and Baki (2019), the effect of dynamic software used for application in the learning of the geometric interpretation of the derivative was examined and it was concluded that the experimental group students who were subjected to the application had higher academic success.…”
Section: Discussion Conclusion and Suggestionssupporting
confidence: 54%